Streptomyces sp. Mitigates Biotic and Abiotic Stress Responses and Stimulates Plant Development - Haggag, Wafaa Mohamed; Gopikrishnan, Venugopal; Soytong, Kasem (My University, 2026)
The increasing need of the population for food in limited agricultural land makes it necessary to increase crop production in an environmentally friendly manner. Approximately 20–40% of economic losses in agriculture are attributed to plant pathogens, which include biotic stressors such as fungal and bacterial infections, pests, weeds, and other agents that cause a variety of crop disorders. Abiotic stressors, such as high temperatures, drought, metal poisoning, and soil salinity, are severe constraints on crop productivity. Despite their high effectiveness and ease of use, agrochemicals pose a threat to the environment. A microbial consortium exists in the root zone, and this consortium of microorganisms can resist the impacts of biotic and environmental stresses on plants, resulting in sustainable agricultural productivity. To achieve sustainable crop productivity, rhizosphere and plant periphyton engineering, the best technology for enhancing crop production, requires the identification of a variety of microorganisms with different potentials. Beneficial microorganisms known as plant growth-promoting rhizobacteria reside close to plant roots and increase plant development. The gram-positive bacterium Streptomyces sp., often known as plant growth-promoting rhizobacteria, can increase plant development and resistance to adverse climatic conditions. Streptomyces sp. is renowned for its ability to produce a wide range of antimicrobials, as well as a large number of secondary and physiologically active metabolites. These metabolites are necessary for plants to withstand environmental stresses and can also function as biological pesticides by triggering plant defense mechanisms against pathogen invasion. Furthermore, they have a strong ability to increase plant development. To reduce the negative effects of biotic and environmental pressures, as well as climate change, this study proposes novel applications of beneficial Streptomyces and their active second-generation metabolites in agriculture.
Keywords: Abiotic stresses; Biotic; Plant development; Streptomyces sp.